2010
DOI: 10.1089/neu.2010.1321
|View full text |Cite
|
Sign up to set email alerts
|

Noxious Colorectal Distention in Spinalized Rats Reduces Pseudorabies Virus Labeling of Sympathetic Neurons

Abstract: The retrograde transsynaptic tracer pseudorabies virus (PRV) has been widely used as a marker for synaptic connectivity in the spinal cord. Notably, the PRV-152 construct expresses enhanced green fluorescent protein (EGFP). We recently reported a significant attenuation of PRV-152 labeling of the intermediolateral cell column (IML) and celiac ganglia after complete T4 spinal cord transection versus sham injury in rats at 96 h after PRV-152 inoculation of the left kidney. Here we found a significant increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
1
8
1
Order By: Relevance
“…PRV transneuronal labeling has not been shown definitively to be associated with function; however, it is noteworthy that we 1,70 and others 51,52 have observed delayed first-order labeling of motoneurons after SCI. Although this may be associated in part with deafferentation, it is more likely a reflection of neuromuscular junction dynamics post-injury 71 or changes in PRV receptors.…”
contrasting
confidence: 58%
See 2 more Smart Citations
“…PRV transneuronal labeling has not been shown definitively to be associated with function; however, it is noteworthy that we 1,70 and others 51,52 have observed delayed first-order labeling of motoneurons after SCI. Although this may be associated in part with deafferentation, it is more likely a reflection of neuromuscular junction dynamics post-injury 71 or changes in PRV receptors.…”
contrasting
confidence: 58%
“…[47][48][49][50] Trans-synaptic tracing techniques 1,4,51,52 were used in the present study to anatomically characterize the distribution of interneurons within the ECRL motor circuit. The results show an extensive bilaterally distributed propriospinal network with pre-motor interneurons being prominent in the intermediate gray matter (laminae VII and X) of the midcervical spinal cord, ipsilateral to the motoneuron pool.…”
Section: Forelimb Spinal Motor Circuitry In Spinally Intact Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is a growing use of PRV to transynaptically trace neuronal connectivity following SCI (Bareyre, et al, 2004, Duale, et al, 2009, Duale, et al, 2010, Im, et al, 2008, Kim, et al, 2002, Lane, et al, 2009, Lane, et al, 2008b, Yu, et al, 2003), we (Lane, et al, 2009) and others (Duale, et al, 2009, Duale, et al, 2010) have reported a reduction in the extent of first-order PRV neuronal infection as a function of time after SCI. In other on-going studies (unpublished), we have determined that the rate of infection is delayed such that maximum first-order labeling of PhMNs occurs 24 hours later than normal.…”
Section: Resultsmentioning
confidence: 85%
“…Many physiological, neurophysiological, neurochemical, histological, imaging and behavioral outcome measures are presently available that can provide more comprehensive, quantitative assessments of motor, autonomic, and sensory functions at different spinal levels. There are also methods available for assessing neuroprotection relative to specific functions and their underlying motor neuron and intraspinal substrate circuits using conventional (McKenna et al, 2000) and, when feasible, transneuronal (Bareyre et al, 2004; Lane et al, 2008b, 2009; Duale et al, 2009, 2010) retrograde tracing in combination with anterograde tracing.…”
Section: Special Design Considerations For Acute/subacute Preclinicalmentioning
confidence: 99%